"Suits you sir! ‐‐ choosing the right style of SE before tailoring to fit": Using Functional Failure Modes and Effects Analysis to guide selection of the right Systems approach. Issue 1 (28th October 2015) - Kemp, Duncan; Beasley, Richard; Williams, Samantha
Abstract: Despite significant evidence that Systems Engineering (SE) adds value, take‐up is patchy. There is a growing volume of evidence that the 'understand‐plan‐do' paradigm behind conventional Systems Engineering only works in some circumstances. We have seen situations where SE has either over‐complicated the solution or was unable to deliver quickly enough. Applying SE in these situations leads to both a specific failure and damages the credibility of SE more broadly. This paper: Proposes a new, two phase, tailoring process. Select an approach suitable for the situation then (if appropriate) decide what SE to do. Includes a Functional Failure Modes and Effects Analysis (FFMEA), which identifies functional failures modes, effects and mitigation activities applicable to the first stage of the tailoring process. Illustrates the FFMEA with 7 case studies. The proposed mitigations provide a high level blueprint for an enterprise that implements conventional SE, when, and only when, appropriate.